Konseling Kelompok Berbasis Pendekatan Adlerian Untuk Meningkatkan Rasa Percaya Diri Peserta Didik - Febriani, Rahmi Dwi; Neviyarni, Neviyarni; Karneli, Yeni; Netrawati, Netrawati (Jurnal Aplikasi IPTEK Indonesia, 2021)
Students have various problems, one of which is related to self-confidence that needs to be explored and eradicated. School counselors have challenges in alleviating students' trust problems in schools. Counselors are required to have competence in counseling services in schools. The purpose of this study is to provide an overview of group counseling based on the Adlerian approach to increase students' self-confidence. This research uses a qualitative research method with a literature review approach. A literature study is a method used to collect data or sources related to the Adlerian approach that was adopted in a study and then analyzed by the descriptive analysis method. The Adlerian approach is one of the most popular approaches to group counseling in practice. In this article, we will discuss the analysis of group counseling based on the Adlerian approach to increase students' self-confidence. Based on the analysis of the group counseling approach, the Adlerian approach can increase students' self-confidence.